Effect of cooperative inspection activities on the performance of farmers cooperative societies in anambra state, nigeria - Odigbo; Chinedu Francis; Agbasi; Obianuju Emmanuela (Journal of Management and Science, 2022)
This study examined the effect of cooperative inspection activities on the performance of Farmers cooperative societies in Anambra State. The study Specifically modeled the effect of cooperative education and training, frequent inspection, inspectors frequent visitation and inspection activities on total output of Farmers cooperative societies, membership strength of Farmers,community investment of Farmers cooperative societies and members participation of Farmers Cooperative Societies in Anambra State respective using a descriptive survey design on a sample of 96 management committees of selected cooperative societies in Anambra State. The study was anchored on Systems Theory propounded by Ludwig von Bertalanffy in 1930s. Data collected for the study were analyzed using descriptive statistics and chi-square statistics. The results from the analysis revealed that cooperative education and training has significant influence on the total output of Farmers cooperative societies in Anambra State. Cooperative Societies activities have significant effect on the membership strength of Farmers cooperative societies in Anambra State. Inspectors’ frequent visitation has no significant influence on the community investment of Farmers cooperative societies in Anambra State. Inspection activities have significant influence on members’ participation of Farmers Cooperative Societies in Anambra State. Based on the findings, the following are recommended; to increase farmers output, cooperative societies should sustain cooperative education and training because it was found to have significant influence on the total output of Farmers cooperative societies in Anambra State. Cooperative societies should advertise their activities so that non members will its benefits and key into their activities by subscribing to its membership. Areas of cooperative community investment should be specifies to enable inspectors focus that. This will help improve the contributions of cooperative to community investment.Inspection activities should be done regularly as it has a positive influence on the participation of members.